Utilization Of E-Learning In Facing Learning Loss In The New Normal Era: A Study On Islamic Religious Education (Pai) In Junior High School In Malang City - Dina Mardiana (FALASIFA : Jurnal Studi Keislaman, 2022)
The current situation of the COVID-19 pandemic, which has entered the New Normal Era, has harmed education in the form of learning loss. This research examines e-learning in dealing with learning loss in Islamic Religious Education (PAI) subjects at Al-Irsyad Junior High School (SMP-AI) in Malang City. This research uses a qualitative approach with the type of case study, whereas analyzes data through the interactive technique of Miles, Hubermann, and Saldana. The conclusion of this research states that e-learning at SMP AI Malang focuses on two things in dealing with learning loss. They are: First, upgrading learning technology, which is centered on maximizing the role of the web academic.alirsyadmalang.org. Second, increasing the aspect of students' learning motivation in following the e-learning process implemented by SMP AI Malang. Efforts to use e-learning can be considered as one of the solution options that educational institutions can carry out in dealing with the phenomenon of learning loss during the New Normal Era.